2013
DOI: 10.1155/2013/703924
|View full text |Cite
|
Sign up to set email alerts
|

Visual Hallucinations in PD and Lewy Body Dementias: Old and New Hypotheses

Abstract: Abstract. Visual Hallucinations (VH) are a common non-motor symptom of Parkinson's Disease (PD) and the Lewy body dementias (LBD) of Parkinson's disease with dementia (PDD) and Dementia with Lewy Bodies (DLB). The origin of VH in PD and LBD is debated: earlier studies considered a number of different possible mechanisms underlying VH including visual disorders, Rapid Eye Movement (REM) Sleep Intrusions, dysfunctions of top down or bottom up visual pathways, and neurotransmitter imbalance. More recently newer h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 131 publications
(208 reference statements)
4
80
1
Order By: Relevance
“…These functional attributes of the memory perception network and the enhancement of its activity may be involved in the generation of visual hallucination in DLB. Contrary to our results, many previous DLB studies reported visual hallucination patients in association with worse visuospatial and cognitive function compared with patients without visual hallucination [94, 95]. However, while we used drug-free early-stage DLB patients, in these studies, visual hallucination patients tended to have more advanced stage of the disease than patients without visual hallucination and were treated with drugs such as AchEI, levodopa, and antipsychotics, which affect DLB symptoms and brain functions.…”
Section: Discussioncontrasting
confidence: 99%
“…These functional attributes of the memory perception network and the enhancement of its activity may be involved in the generation of visual hallucination in DLB. Contrary to our results, many previous DLB studies reported visual hallucination patients in association with worse visuospatial and cognitive function compared with patients without visual hallucination [94, 95]. However, while we used drug-free early-stage DLB patients, in these studies, visual hallucination patients tended to have more advanced stage of the disease than patients without visual hallucination and were treated with drugs such as AchEI, levodopa, and antipsychotics, which affect DLB symptoms and brain functions.…”
Section: Discussioncontrasting
confidence: 99%
“…14 These deficits of visual perception and attentional control are thought to cause visual hallucinations and illusions through an imbalance of top-down expectations and bottom-up visual processing (see ref. 15 for a review). Consistent with the neuropsychological findings, visual hallucinations are associated with reduced grey matter volume in the visual system, hippocampus, frontal regions ( particularly lateral frontal cortex) and cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…39 As in Alzheimer's and Parkinson's, hallucinations are common in Lewy body dementia and are most frequently visual in nature. 40 Visual hallucinations early in the course of the disease, in fact, are considered to be a core feature of Lewy body dementia. 41 A recent study found that 63% of patients experienced visual hallucinations, 17 and another found that 78% of patients had hallucinations, 56% had misidentifications, and 25% had delusions.…”
Section: Alzheimer's Disease and Other Dementiasmentioning
confidence: 99%